Islamic Thought of Kh. M. Hasyim Asy'ari in Fostering Love for the Motherland - Lubis, Ardiansyah; Bakar, M. Yunus Abu; Fuad, Ah. Zakki (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This research aims to analyze KH. M. Hasyim Asy'ari's Islamic thought in fostering patriotism, as well as his contribution to Indonesian education and community development. Using a Systematic Literature Review (SLR) approach with PRISMA guidelines, this research includes article searches through Scopus and Google Scholar, which collected 315 relevant articles, which were then analyzed using the VOSviewer application to map thematic linkages. The article selection and analysis process was rigorous to ensure the quality and relevance of the findings. This research identified and summarized relevant literature regarding KH. M. Hasyim Asy'ari's contribution in promoting the values of nationalism and patriotism. The main findings of the research show that KH. M. Hasyim Asy'ari's thoughts, such as Ruh al-Jihad, Ruh al-Ittihad, and the principle of hubbub within minal iman, provide important inspiration to generate a sense of nationalism, especially among the younger generation. His role in the establishment of the Tebuireng Islamic Boarding School, the introduction of an educational curriculum that combines religion and general science, and the establishment of Nahdlatul Ulama as a forum for the struggle for independence contributed greatly to instilling religious and national values. However, this research also notes the challenges in implementing his thoughts in the era of globalization, including the influence of foreign cultures, the development of technology and information, and the increasing radicalization that can threaten the spirit of nationalism. This research contributes to the development of knowledge regarding the strengthening of nationalist values based on moderate and contextual Islamic teachings.